2017
DOI: 10.7197/223.v39i32356.369027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the cyclooxygenase-2 inhibitor tenoxicam on pentylenetetrazole-induced epileptic seizures in rats

Abstract: SUMMARYObjective: Epilepsy is a short-term paroxysmal disturbances of brain functions observed between sudden, abnormal and hypersynchronization discharges and seizures of a group of neurons in the central nervous system. The nonsteroidal anti-inflammatory tenoxicam is chemical agent that selectively inhibits type 2 cyclooxygenase (COX2), which converts arachidonic acid to prostaglandins (PGs). The aim of this study was to investigate the effect of the cyclooxygenase-2 inhibitor tenoxicam on pentylenetetrazole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Studies in rats have also closely linked HMGB1 to reduced cognitive abilities related to neuroinflammation, TBI, and epilepsy [28,29]…”
Section: Role Of High Mobility Group Box 1 (Hmgb 1) In Epilepsymentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in rats have also closely linked HMGB1 to reduced cognitive abilities related to neuroinflammation, TBI, and epilepsy [28,29]…”
Section: Role Of High Mobility Group Box 1 (Hmgb 1) In Epilepsymentioning
confidence: 99%
“…Two COX isozymes are known: COX-1, which is constitutively produced in almost all body tissues, and COX-2, predominantly produced in brain tissues after various insults, thus contributing to the brain inflammation involved in the long-term consequences of such insults [28]. Experimental studies conducted on rat models have shown a significant protective role of selective COX-2inhibitors against epilepsy and neuronal damage despite the unclear role of COX-2 on the pathogenesis of epilepsy [29]. Because of this neuroprotection role, celecoxib, a selective COX-2-inhibitor non-steroidal anti-inflammatory medication, is currently prescribed as an antiepileptogenesis disease-modification drug following brain insults like status epilepticus, cerebral ischemic injuries or head trauma.…”
Section: Cyclooxygenase (Cox) Role In Epilepsymentioning
confidence: 99%
See 1 more Smart Citation